Competitividad empresarial del sector cafetalero exportador de México - Hernández Tolentino, Alicia (Universidad Michoacana de San Nicolás de Hidalgo, 2020)
This research aimed to determine the influence of the variables strategic planning, production and operations, quality, commercialization, accounting and finance, human resources, environmental management and information systems in the business competitiveness of the Mexican coffee export sector. To achieve the aforementioned objective, a theoretical review on trade and competitiveness was first made, then the situation and trends of the coffee industry were addressed; regarding the methodology, an analysis with descriptive statistics and a factor analysis were made. After the analysis and interpretation of the results, the conclusions and recommendations pertinent to this research were finally reached. Regarding the results, the hypothesis proposed was verified, that is, the variables, strategic planning, production and operations, quality, commercialization, accounting and finance, human resources, environmental management and information systems positively influence the business competitiveness of the Mexican coffee export sector. The investigation concludes that business competitiveness is mainly based on quality, human resources and production and operations.

Esta investigación tuvo por objetivo determinar la influencia que tienen las variables planeación estratégica, producción y operaciones, calidad, comercialización, contabilidad y finanzas, recursos humanos, gestión ambiental y los sistemas de información en la competitividad empresarial del sector cafetalero exportador de México. Para lograr el objetivo mencionado, primero se hizo una revisión teórica sobre comercio y competitividad, posteriormente, se abordó la situación y tendencias de la industria del café; en cuanto a la metodología, se hizo un análisis con estadística descriptiva y un análisis factorial. Después del análisis e interpretación de los resultados, finalmente se llegó a las conclusiones y recomendaciones pertinentes a esta investigación. En cuanto a los resultados, se comprobó la hipótesis planteada, es decir, las variables, planeación estratégica, producción y operaciones, calidad, comercialización, contabilidad y finanzas, recursos humanos, gestión ambiental y los sistemas de información influyen positivamente en la competitividad empresarial del sector cafetalero exportador de México. La investigación concluye que la competitividad empresarial se basa principalmente en la calidad, los recursos humanos y producción y operaciones.
Instituto de Investigaciones Económicas y Empresariales. Doctorado en Ciencias en Negocios Internacionales
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2622; info:eu-repo/classification/cti/5; ININEE-D-2020-0551; Café; Variables; Empresas exportadoras